2019
DOI: 10.1016/j.dark.2019.100385
|View full text |Cite
|
Sign up to set email alerts
|

Late time transitions in the quintessence field and the H0 tension

Abstract: We consider a quintessence field which transitions from a matter-like to a cosmological constant behavior between recombination and the present time. We aim at easing the tension in the measurement of the present Hubble rate, and we assess the ΛCDM model properly enlarged to include our quintessence field against cosmological observations. The model does not address the scope we proposed. This result allows us to exclude a class of quintessential models as a solution to the tension in the Hubble constant measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 76 publications
0
24
0
1
Order By: Relevance
“…33 Due to this early dark energy-like behaviour, pseudo-scalars are often invoked when building models of quintessence [174][175][176] and inflation [177,178]. 34 The code is available as a Mathematica package at the GIT repository https://github.com/lucavisinelli.…”
Section: Vacuum Realignment Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Due to this early dark energy-like behaviour, pseudo-scalars are often invoked when building models of quintessence [174][175][176] and inflation [177,178]. 34 The code is available as a Mathematica package at the GIT repository https://github.com/lucavisinelli.…”
Section: Vacuum Realignment Mechanismmentioning
confidence: 99%
“…In models where a direct coupling between axion and top quarks exists, the efficiency of the thermal production is enhanced by up to three orders of magnitude [316]. More generally, a direct coupling of the axion to quarks and leptons leads to significant enhancements in ∆N eff [313,318], which might even alleviate the tension between the local direct measurement of H 0 and the model-dependent value of H 0 inferred from the CMBR [176,312], which is currently existing between CMBR [238] and Supernovae measurements [319][320][321]. A prediction for ∆N eff is also useful to set a target for future CMB-S4 surveys [288].…”
Section: Qcd Axions As Dark Radiationmentioning
confidence: 99%
“…There are many attempts to alleviate the issue in the literature (see for an incomplete list of works Refs. [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ] and the recent overview in [ 79 , 80 ]). It has been recently discussed [ 81 , 82 ] that a transition in absolute magnitude for SnIa can also explain the apparent tension between the local and CMB measurements of the Hubble parameter .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the value of the Hubble constant H 0 predicted by the cosmic microwave background (CMB) Planck data [2,5] within the framework of the standard CDM model is in serious disagreement with the direct local distance ladder measurements [23][24][25][26]. This tension becomes even more compelling as it worsens (relieves only partially) when the is replaced by the simplest minimally coupled single-field quintessence (phantom or quintom models), see [27][28][29][30] and [31] for further references. Surprisingly, it has been reported that the H 0 tension -as well as a number of other persistent low-redshift tensions -may be alleviated by a dynamical dark energy (DE) whose density can assume negative values or vanish at high redshifts [31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%